2015
DOI: 10.1002/pbc.25581
|View full text |Cite
|
Sign up to set email alerts
|

Poor bone health at the end of puberty in childhood cancer survivors

Abstract: Decreased BMD was prevalent in our study cohort. Endocrine dysfunction was found to be a significant risk factor, and it should be managed in survivors to ensure future bone health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…A total of 13,442 subjects were represented by the included studies. The majority of the studies were conducted in the following developed countries ( n = 52, 88%): Japan [ 27 , 29 , 30 , 33 , 35 , 38 40 , 42 , 43 , 45 , 49 , 54 , 57 , 59 , 61 , 63 , 64 , 67 69 , 78 , 80 ] ( n = 24, 41%), South Korea [ 24 , 26 , 31 , 32 , 34 , 37 , 46 , 53 , 55 , 56 , 58 , 60 , 62 ] ( n = 13, 22%), Hong Kong [ 41 , 50 – 52 , 72 – 75 , 76 , 77 , 79 , 81 , 82 ] ( n = 12, 20%), Taiwan [ 47 , 48 ] ( n = 2, 3%), Singapore [ 36 ] ( n = 1, 1.5%). Only seven studies (12%) were conducted in developing countries [ 25 , 28 , 44 , 65 , 66 , 70 , 75 ] (Thailand and Malaysia).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13,442 subjects were represented by the included studies. The majority of the studies were conducted in the following developed countries ( n = 52, 88%): Japan [ 27 , 29 , 30 , 33 , 35 , 38 40 , 42 , 43 , 45 , 49 , 54 , 57 , 59 , 61 , 63 , 64 , 67 69 , 78 , 80 ] ( n = 24, 41%), South Korea [ 24 , 26 , 31 , 32 , 34 , 37 , 46 , 53 , 55 , 56 , 58 , 60 , 62 ] ( n = 13, 22%), Hong Kong [ 41 , 50 – 52 , 72 – 75 , 76 , 77 , 79 , 81 , 82 ] ( n = 12, 20%), Taiwan [ 47 , 48 ] ( n = 2, 3%), Singapore [ 36 ] ( n = 1, 1.5%). Only seven studies (12%) were conducted in developing countries [ 25 , 28 , 44 , 65 , 66 , 70 , 75 ] (Thailand and Malaysia).…”
Section: Resultsmentioning
confidence: 99%
“…• Deficiencies in growth hormone (82%), gonadotrophic hormone (68%), adrenocorticotropic hormone (64%), thyroid hormone (75%), and antidiuretic hormone (68%) • Lower BMI • Later starting age of adult growth hormone replacement • Male sex • Low lean mass Miyoshi [ 59 ] Japan 53 0% Mixed 6.3 [0–12.9] 17.4 [4.0–29.6] 8.8 [2.3–26.1] post-tx ✓ (100%) ✓ (57%) ✓ (43%) Anti-Mullerian hormone assay, FSH assay, pubertal development • Decreased anti-Mullerian hormone level (53%) • Increased FSH level (30%) • Abnormal breast development (17%) •No spontaneous menstruation (26%) • Total body irradiation • Spinal radiation • Radiation of pelvis or its vicinity Choi [ 58 ] Korea 78 44% Leukemia Male: 7.2 ± 3.8 Female: 7.7 ± 3.9 Male: 11.6 ± 3.4 Female: 13.0 ± 3.3 Male: 4.4 ± 2.5 post-dx Female: 5.4 ± 3.2 post-dx ✓ (100%) ✓ (62%) ✓ (64%) DEXA, hormones assay, anthropometric measurements • Lumbar BMD standard deviation scores less than −2 (74%) • Longer duration of glucocorticoid treatment for GVHD • HSCT • Chronic GVHD • Reduced BMI Kojima [ 57 ] Japan 49 55.1% Mixed 5.1 [0.2–14.2] 10.7 [6.0–25.3] 5.1 [3.0–14.6] post-tx ✓ (100%) ✓ (22.5%) ✓ (32.7%) Anthropometric measures, glucose and lipid metabolism profiles • Metabolic syndrome in 6%. At least one and more than two components of metabolic syndrome in 37% and 20%, respectively • Hypertriglyceridemia (57%) • Hypertension (54%) • High fasting blood sugar (18%) • Female sex Han [ 56 ] Korea 108 67% Mixed 8.9 ± 4.7 20.3 ± 3.0 9.2 ± 5.2 ...…”
Section: Resultsmentioning
confidence: 99%
“…52 Also, our definition of low BMD is consistent with prior studies by others in survivors. 23,26,27,29,[31][32][33][34][35][36][37][38][39][40]53 An important consideration is the clinical implications of identifying reduced BMD. The COG long-term follow-up guidelines recommend survivors with/at risk of decreased BMD conduct regular weight-bearing activity and ensure adequate vitamin D/calcium intake through diet or supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…26,29,34,35 Low BMD was defined as >1 SD (z-score less than −1) and very low BMD as >2 SDs (z-score less than −2) below age-matched, sex-matched, and race-matched norms, consistent with prior studies in childhood cancer survivors. 13,[36][37][38][39][40]…”
Section: Bmd Evaluationmentioning
confidence: 99%
“…Additionally, the COG‐LTFU Guidelines recommend DXA or QCT scans for hypogonadal patients and state that screening should be considered for patients with growth hormone deficiency . Studies looking at pediatric survivors or adult survivors of pediatric cancers have identified additional risk factors for low BMD that are listed in the COG‐LTFU Guidelines but are independent of an indication to screen such as younger age of diagnosis, older age at treatment, white race, and lower body mass index (BMI) (Supplementary Table S1) …”
Section: Introductionmentioning
confidence: 99%